Library Supervision as a Component of Scientific and Practical Relations between the Library and the Scientist: Current State - Shtan, H. V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective. Library supervision over faculties is a new direction of work, which is being implemented by university libraries in different countries. The work is aimed to study the world and domestic experience of university libraries in the direction of library supervision as a component of scientific and practical relations between the library and the scientist. Methods. The research was conducted on the basis of the analysis of the world literary flow in library information science. The Ukrainian experience is analyzed on the example of implementation of the Library Supervisory Program of the Central Scientific Library of V. N. Karazin Kharkiv National University (CSL KhNU) within the framework of implementation of the University and Library Development Strategy. Results. The most topical issues of concern to the world library community were analyzed: the purpose and options of the librarian-lecturer interaction, the contradictions in the relationship between librarians and scholars, the librarian and information literacy training. The main elements of the Library Supervisory Program of the CSL KhNU are the expanded informing of the representatives of the faculties on the CSL`s possibilities and various forms of individual and group consultations of readers, deepening of inter-organizational interaction. Conclusions. The process of interaction between librarians and higher education departments in the early 21st century, in the context of a holistic and very rapid development of the information society, is urgent and necessary. Given the rational and competent implementation of its basic conditions, which have already been worked out on the basis of foreign experience, it has great potential.